Improving Land Acquisition and Voluntary Land Conversion in Vietnam - World Bank (Washington, DC, 2014)
Successive policies of the Government of Vietnam for economic reform and modernization have helped Vietnam to emerge as one of the world's fastest growing economies. The report provides continued recommendations on improving land policies to ensure efficiency of their practical implementation and to target at both economic development and social sustainability. Policies with regard to voluntary benefits sharing, promoting the participation of communities and social organizations, strengthening the dialogue between the government and the people, creating real consensus across parties related to investment projects, enhancing inspection works by upper level administrative authorities over their lower level ones are analyzed and specifically recommended in this policy note. The policy note includes six chapters: chapter one, is the general introduction of this document; chapter two, focuses on analyzing the prevailing land legislation system for land conversion and the process of land legislation construction to determine its insufficiency issues; chapter three, mainly analyzes the practical implementation of land conversion in Vietnam, based on the analyses of opinions from provincial leaders, investors and affected people; chapter four, carries out analyses of the international and domestic experiences on land acquisition/conversion measures to find the possibilities of application to Vietnam; and chapter five, suggests land policies, legal regulations, and implementation procedures to continuously reform the land acquisition/conversion measures in Vietnam. The policy note ends with the last chapter, which recommends some issues for further studies in the World Bank Vietnam study program on land policies improvement in the upcoming years.